Triggers of violence towards healthcare personnel of a second level care hospital - Puentes-Rojas, Ana Ruth (Universidad de Sonora, 2019)
Introduction: Frequently, health professionals have to deal with violence while performing their duties, putting themselves at risk of receiving physical, psychological and work related consequences. Objective: Determine the factors that trigger violence towards health care personnel. Methodology: Cross-sectional descriptive study, with a sample of 66 people within a second level hospital in México; there was non-probabilistic sampling performed; the “Aggressions towards health professionals within the health care environment” instrument was used. Throughout each phase of the study, the main ethical principles were observed pursuant to the Helsinki’s General Health Act for Research and Declaration. In regards to the data analysis, the SPSS version 20 software was employed, and a descriptive statistical analysis was applied. Results: The factors that trigger violence towards the personnel were the lack of material resources, which is something that was found in 40% of the cases; the notification of the death of the patient in 30% of the cases; and the delay in effective care in 20% of the cases. The main aggressor was the patient. Ninety six percent of the personnel did not abandon their work after the act of violence. Conclusions: The main triggers of violence correspond to the administrative aspects of supplies and resources; this situation should attract the attention of health authorities since the administration of human resources and supplies stays in their competence.